Strategic plan of Kaibigan Development Foundation Inc. for 2011 to 2015 facing the challenges in community building and development - Holazo, Kelly P. (School of Management, University of the Philippines Mindanao, 2011)
Kaibigan Development Foundation Inc. is a non-government organization (NGO) supported by Stanfilco-A Division of Dole Philippines Inc. Its main function is to deliver health services, support poverty alleviation and augmentation programs through livelihood projects, and support environmental conservation programs in the areas where Stanfilco operates and where Stanfilco?s communities? reside. When KDFI was spun off in 1997 from Stanfico, the partnership of the entities continued with a common goal to develop communities where Stanfilco operates. The growing banana industry and company operations resulted in limited manpower and funds. Yet the communities, which they operate, are also increasing and expanding. It is imperative that the organization focused its efforts a well as resources on specific targets (e.g. environment, poverty alleviation etc.). Thus there is a need to examine the organization?s values, competency, its partner?s needs and mandates and vision-mission-goals. The paper used the framework of David (2001) in examining the internal and external environment. The finding showed that the organization has a strong internal position and is responsive to changing external conditions. The study also used Pearce and Robinson?s strategy matrix (2001) in choosing appropriate strategies. From the finding of the analysis, the appropriate grand strategy is a concentrated growth. It is aligned with the need of the organization keeping in mind is limitations. Concentrated Growth is used by firms with the competency of an industry. The global financial crisis contracted the funding of the organization thus there is a need for a more focused target and services. Particularly, KDFI must focus on environmental projects and community development that protects or adhere to environmental concerns. The following are the proposed strategy under concentrated growth. The proposed specific strategies are as follows: Align and Focus of Efforts to Achieve the Mission and Vision: Review and revisit the functions of the people in the organization including policies and standards. Realign their vision and mission with the vision of Stanfilco. Human resource development is also necessary particularly the CDOs. Integrate-Linkage: Convergence of efforts with other NGOs and LGUs is necessary if the organization. Media promotion is also important for getting funds. Create a culture of innovativeness: encourage innovation of services such as development of green enterprise development, joint environmental research endeavors with international organizations and even local government units such as solid waste management. These are but some of the strategies that need to be implemented focusing on environmental concerns. The paper shall open possibilities for other projects that are linked directly to environmental issues.